Implications of the Thermodynamic Response of Soil Mineralization, Respiration, and Nitrification on Soil Organic Matter Retention - Taylor, Anne E.; Ottoman, Camille; Chaplen, Frank (Frontiers in Microbiology, 2021)
Considerable research has shown that modifications in global temperature regimes can lead to changes in the interactions between soil respiration and the sequestration of C and N into soil organic matter (SOM). We hypothesized that despite the interconnected nature of respiration, net N mineralization, and nitrification processes, that there would be differences in their thermodynamic responses that would affect the composition of inorganic soil N and the potential for retention of N in SOM. To test this hypothesis, soil respiration, N mineralization and nitrification responses were evaluated during constant temperature incubations at seven temperatures (4 – 42oC) in tilled and no-till soils from two major agroecological zones in Oregon; Willamette Valley, and Pendleton located in the Columbia River Basin. We observed (1) significant thermodynamic differences between the three processes in all soils, (2) a distinctly different thermodynamic profile in Willamette vs. Pendleton, and (3) a dynamic response of Topt (optimal temperature for activity), and Tsmax (temperature of greatest rate response to temperature), and temperature sensitivity (∆Cp‡) over the incubation time course, resulting in shifts in the thermodynamic profiles that could not be adequately explained by changes in process rates. We found that differences in contributions of ammonia oxidizing archaea and bacteria to nitrification activity across temperature helped to explain the thermodynamic differences of this process between Willamette and Pendleton soils. A two-pool model of SOM utilization demonstrated that the dynamic thermodynamic response of respiration in the soils was due to shifts in utilization of labile and recalcitrant pools of C; and that the respiration response by Pendleton soils was more dependent upon contributions from the recalcitrant C pool resulting in higher Topt and Tsmax than Willamette soils. Interestingly, modeling of N mineralization using the two-pool model suggested that only the recalcitrant pool of SOM was contributing to N mineralization at most temperatures in all soils. The difference in labile and recalcitrant SOM pool utilization between respiration and N mineralization may suggest that these processes may not be as interconnected as previously thought.